2019
DOI: 10.1021/acs.est.9b00574
|View full text |Cite
|
Sign up to set email alerts
|

Development of Prediction Models on Base-Catalyzed Hydrolysis Kinetics of Phthalate Esters with Density Functional Theory Calculation

Abstract: Many phthalate esters (PAEs) are chemicals of high production volume and of toxicological concern. The second-order rate constant for base-catalyzed hydrolysis (k B) is a key parameter for assessing environmental persistence of PAEs. However, the k B values for most PAEs are lacking, and the experimental determination of k B encounters various difficulties. Herein, density functional theory (DFT) methods were selected by comparing empirical k B values of five PAEs and five carboxylic acid esters with the DFT-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…The QM/MM calculation was carried out on the ChemShell platform, combined with TURBOMOLE (dealing with the QM region) and DL-POLY program (dealing with the MM region) with the CHARMM27 force field to generate the optimized structure and QM/MM energy. The QM region was treated by the DFT method, and the MM region was treated by the CHARMM27 force field. In the calculation of QM/MM, the linking hydrogen atom method, charge shift model, and electrostatic embedding scheme were used.…”
Section: Methodsmentioning
confidence: 99%
“…The QM/MM calculation was carried out on the ChemShell platform, combined with TURBOMOLE (dealing with the QM region) and DL-POLY program (dealing with the MM region) with the CHARMM27 force field to generate the optimized structure and QM/MM energy. The QM region was treated by the DFT method, and the MM region was treated by the CHARMM27 force field. In the calculation of QM/MM, the linking hydrogen atom method, charge shift model, and electrostatic embedding scheme were used.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies investigated the effects of side chain type (alkyl or aryl) on hydrolysis kinetics of PAEs and organophosphate triesters, and also indicated that the aryl side chains are more vulnerable to the base-catalyzed hydrolysis than the alkyl side chains. 23,59 The current study further unveils the effects of side chain length on the base-catalyzed hydrolysis kinetics of the parabens.…”
Section: ■ Results and Discussionmentioning
confidence: 61%
“…The integral equation formalism of the polarized continuum model (IEFPCM) 49 and SMD 40 were widely used implicit solvation models and have been testified with good performance in many studies on hydrolysis. 23,25,27,28 These two implicit solvation models were initially tested for the reference compounds as well. Effects of explicit water molecules on the hydrolysis kinetics were also evaluated.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations